La migración a Costa Rica: características socioeconómicas - Vargas Vargas, José Joaquín (2007)
The migration to Costa Rica wasn‘t only the coming of stranges, it is an impact to our country. This analysis pretends to serve an objective vision to the relationship between the immigrants and the social and socio-economic development of Costa Rica.